Improving Australia's renewable energy project policy and planning: A multiple stakeholder analysis. (September 2015) - Martin, Nigel; Rice, John
Abstract: Renewable Energy (RE) is part of Australia's and the world's energy supply matrix with over A$100 billion spent annually on RE projects since 2007. Businesses seeking to invest in RE projects, particularly in the wind and solar energy sectors, may face an onerous collection of planning approvals and permitting processes that impede investment and implementation. In this study, we draw on international and domestic stakeholder inputs to a governmental inquiry in Australia to show how RE projects might be approved in shortened timeframes with reduced associated costs. The process mapping and stakeholder analysis demonstrates that RE supply projects can benefit from standardized approval processes and documentation, a 360° deep engagement with stakeholders, and expanded electricity grid access in resource areas, augmented through supportive public policy and planning frameworks. In addition, stakeholder objections to project approval and implementation streamlining were used to contrast the efficacy of the proposed changes in policy. Highlights: Highlights the over A$200 billion spent annually on global RE projects. Describes a typical two stage, multi-layered governance RE project approval process. Exposes long 3 year and multi-million dollar cost approvals for RE projects. Identifies multi-million dollar remote grid connections as an RE project impediment. Outlines RE project policy and guidelines shortcomings and proposed improvements.